2013
DOI: 10.3382/ps.2012-02569
|View full text |Cite
|
Sign up to set email alerts
|

Effects of balanced dietary protein levels on egg production and egg quality parameters of individual commercial layers

Abstract: The effects of a series of balanced dietary protein levels on egg production and egg quality parameters of laying hens from 18 through 74 wk of age were investigated. One hundred forty-four pullets (Bovans) were randomly assigned to individual cages with separate feeders including 3 different protein level series of isocaloric diets. Diets were separated into 4 phases of 18-22, 23-32, 33-44, and 45-74 wk of age. The high protein (H) series contained 21.62, 19.05, 16.32, and 16.05% CP, respectively. Medium prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 21 publications
5
30
1
2
Order By: Relevance
“…Because the weight of the eggs from the hens fed protease B was lower than that of the eggs from positive-control hens, we can assume that only the lower albumen height of the protease-B hens was responsible for its lower Haugh unit value, since egg weight is negatively associated with the Haugh unit while albumen height is positively associated. Contrary to our results, Shim et al (2013) described an increase in the Haugh unit after reduction of dietary crude protein. This response was probably a consequence of the lower egg weight; nevertheless, because the albumen height was not provided by the authors, our comparison remains limited.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Because the weight of the eggs from the hens fed protease B was lower than that of the eggs from positive-control hens, we can assume that only the lower albumen height of the protease-B hens was responsible for its lower Haugh unit value, since egg weight is negatively associated with the Haugh unit while albumen height is positively associated. Contrary to our results, Shim et al (2013) described an increase in the Haugh unit after reduction of dietary crude protein. This response was probably a consequence of the lower egg weight; nevertheless, because the albumen height was not provided by the authors, our comparison remains limited.…”
Section: Discussioncontrasting
confidence: 56%
“…While different assumptions could be made to explain the better performance by protease A, the results of all treatments led to one big question: does protease A alone have a more suitable nutritional matrix than protease B alone, or is the actual nutritional contribution of the combination of protease A and phytase greater than the nutritional contribution of protease alone? Because different levels of interaction between phytases and multienzyme complexes with proteases have been described for broilers and hens (AL-SAFFAR et al, 2013;OLUKOSI et al, 2010;TIWARI et al, 2010), it seems reasonable to consider the second option as a valid statement. In this case, increased or decreased affinity between enzymes under study may be responsible for the different responses observed for each protease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers reported the general tendency increase egg production and egg weight with the increase of protein levels in the diets (Gunawardana et al, 2008;King'ori et al, 2010;Mohiti-Asli et al, 2012;Shim et al, 2013). Some other researchers reported that egg production and egg weight was not affected by feeding low crude protein (Cho et al, 2004;Khajali et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The composition of hen diet has an effective factor on egg production (Khajali et al, 2008;Perez-Bonilla et al, 2012), egg weight (Whitehead et al, 1991, Zimmerman 1997Shim et al, 2013) and hatching characters (Danicke et al, 2000) in poultry.…”
Section: Introductionmentioning
confidence: 99%